Scaling Up Disability Inclusion in Water Projects : Case Study of PAMSIMAS - Koyama, Ayumi (World Bank, Washington, DC, 2020)
More than 1 billion people worldwide, or 15 percent of the global population, have some form of disability, with higher rates in low-income countries. This number is expected to rise significantly due to factors such as aging populations, conflict, and the impacts of climate change. For these reasons, disability-inclusive development is of interest to the Water Global Practice of the World Bank, to the World Bank’s twin goals of reducing extreme poverty and promoting shared prosperity, and to Sustainable Development Goal (SDG) 6 (to ensure the availability and sustainable management of water and sanitation for all). SDG 6 relates not only to water and sanitation access by persons with disabilities, but also to their engagement in the management of water and sanitation. The new Environmental and Social Framework requires borrowers to look specifically at persons with disabilities as part of any social assessments, and the proposed International Development Association (IDA) 19 policy ensures disability inclusion in projects.